Web, Artificial Intelligence and Network Applications Proceedings of the Workshops of the 33rd International Conference on Advanced Information Networking and Applications (WAINA-2019) - Barolli, Leonard; Takizawa, Makoto; Xhafa, Fatos; Enokido, Tomoya; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The aim of the book is to provide latest research findings, innovative research results, methods and development techniques from both theoretical and practical perspectives related to the emerging areas of Web Computing, Intelligent Systems and Internet Computing. As the Web has become a major source of information, techniques and methodologies that extract quality information are of paramount importance for many Web and Internet applications. Data mining and knowledge discovery play key roles in many of today's prominent Web applications such as e-commerce and computer security. Moreover, the outcome of Web services delivers a new platform for enabling service-oriented systems. The emergence of large scale distributed computing paradigms, such as Cloud Computing and Mobile Computing Systems, has opened many opportunities for collaboration services, which are at the core of any Information System. Artificial Intelligence (AI) is an area of computer science that build intelligent systems and algorithms that work and react like humans. The AI techniques and computational intelligence are powerful tools for learning, adaptation, reasoning and planning. They have the potential to become enabling technologies for the future intelligent networks. Recent research in the field of intelligent systems, robotics, neuroscience, artificial intelligence and cognitive sciences are very important for the future development and innovation of Web and Internet applications.
Adaptive Waveform Design of Polarimetric Radar for Extended Targets in Signal-Dependent Clutter -- CRAWL: A Trace Routing Algorithm based on Hybrid Two-layer Topology -- Design and Implementation of IoT based Automatic Class Attendance Monitoring System using ComputerVision and Embedded Linux Platform -- An Indoor 3D Positioning Technology based on NB-IoT -- Consideration of Implementation Method for the Cloud Type Virtual Policy Based Network Management Scheme for the Specific Domain -- A Model of Virtual Machines to Support Storage Processes -- Energy Efficient Scheduling of Smart Home -- Minimizing Daily Cost and Maximizing User Comfort using a New Metaheuristic Technique -- Efficiency Analysis of TFHE Fully Homomorphic Encryption Software Library Based on GPU -- NADEEM: A Novel Reliable Data Delivery Routing Protocol for Underwater WSNs.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence